2015
DOI: 10.1177/0363546515613517
|View full text |Cite
|
Sign up to set email alerts
|

Medial Femoral Condyle Cartilage Defect Biomechanics

Abstract: These biomechanical findings corroborate clinical studies that have noted worse outcomes after microfracture in patients with BMI ≥30 and cartilage defects of size ≥2 cm(2). Further clinical studies are needed to compare microfracture with other cartilage restoration procedures in these patient subsets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…Ultimately, prolonged wait times are a concern in the young, active patient population that typically requires this procedure, as even small full-thickness lesions experience increased force at the base and periphery of the defect and can possibly progress in size with continued weightbearing. 6 , 7 Fresh OCA cores represent an ideal alternative to standard graft matching for small femoral condyle lesions for myriad reasons. Similar to fresh hemicondylar allografts, these cores provide a mature hyaline cartilage/bone construct with 80% absolute viability in the superficial, middle, and deep chondral layers.…”
Section: Discussionmentioning
confidence: 99%
“…Ultimately, prolonged wait times are a concern in the young, active patient population that typically requires this procedure, as even small full-thickness lesions experience increased force at the base and periphery of the defect and can possibly progress in size with continued weightbearing. 6 , 7 Fresh OCA cores represent an ideal alternative to standard graft matching for small femoral condyle lesions for myriad reasons. Similar to fresh hemicondylar allografts, these cores provide a mature hyaline cartilage/bone construct with 80% absolute viability in the superficial, middle, and deep chondral layers.…”
Section: Discussionmentioning
confidence: 99%
“…55,56 A larger lesion size as risk factor is in accordance with biomechanical studies that have shown that defects larger than 2 cm 2 increase the load on the base of the defect as well as on the rim. 57 This will potentially negatively influence the development of the repair tissue in the defect and the progression of rim cartilage deformation, resulting in the pothole effect as mentioned before. 58 The same biomechanics apply to lesion location as a prognostic factor.…”
Section: Discussionmentioning
confidence: 99%
“…75 , 81 , 82 It has been hypothesized that the treated defect is unable to withstand the detrimental pothole effect. 45 In addition, the subchondral bone (SB) starts thickening and forms cysts due to aging, OA, or chronic cartilage defects. 26 , 72 The standard MF awl causes widespread microarchitecture disturbances in the SB, leading to further sclerosis 27 and cyst formation after MF, 76 with good correlation between the severity of SB changes and poor clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%